2021
DOI: 10.3390/e23020141
|View full text |Cite
|
Sign up to set email alerts
|

Knotting the MECO Network

Abstract: The Conferences of the Middle European Cooperation in Statistical Physics (MECO) were created as an attempt to establish and maintain an exchange between scientists in the fields of statistical and condensed matter physics from Western and Eastern countries, overcoming the hurdles of the Iron Curtain. Based on personal remembrance and historical resources, the genesis and further development of MECO meetings is described. The annual meetings were interrupted in 1991 by the Yugoslav War but were re-established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 69 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…The Conference of the Middle European Cooperation in Statistical Physics was born from the idea to bridge the gap between the Eastern and Western European scientific community divided by the Iron Curtain [12]. From the very beginning, special attention was paid to the geography of participants: it was decided to change the location every year and, in addition, to ensure that the organizations hosting the conference were chosen each time on the other side of the invisible line that separated one part of Europe from another [12]. Due to these political-geographical aspects, the MECO conference can be considered as a symbolic bridge for scientific contacts not only at the personal level, but also at the level of countries.…”
Section: Meco Conferencesmentioning
confidence: 99%
See 2 more Smart Citations
“…The Conference of the Middle European Cooperation in Statistical Physics was born from the idea to bridge the gap between the Eastern and Western European scientific community divided by the Iron Curtain [12]. From the very beginning, special attention was paid to the geography of participants: it was decided to change the location every year and, in addition, to ensure that the organizations hosting the conference were chosen each time on the other side of the invisible line that separated one part of Europe from another [12]. Due to these political-geographical aspects, the MECO conference can be considered as a symbolic bridge for scientific contacts not only at the personal level, but also at the level of countries.…”
Section: Meco Conferencesmentioning
confidence: 99%
“…This number is naturally limited by the time frame of the conference program as well as the physical limitations of the venue. Traditionally, the MECO conference moves from one country to another, accommodating all participants in one place for these few days [12]. Thus, a saturation of the annual number of authors can be observed: usually about 195 researchers participate, and the geography of one meeting usually includes 26 countries.…”
Section: Meco Conferencesmentioning
confidence: 99%
See 1 more Smart Citation